Improved Sensitivity in Comparative Genomic Hybridization Analysis of DNA Heteroploid Cell Mixtures after Pre-Enrichment of Subpopulations by Fluorescence Activated Cell Sorting - Jacob Larsen; Maria Kirchhoff; Hanne Rose; Tommy Gerdes; Jan Maahr; Claes Lundsteen; Jørgen K. Larsen (Analytical Cellular Pathology)
Cytogenetic analysis of solid tumors with comparative genomic hybridization (CGH) is hampered by the dilution of DNA from individual tumor subpopulations with DNA from other cells. We investigated to what extent this dilution effect can be alleviated using fluorescence activated cell sorting (flow sorting) of experimental DNA heteroploid cell mixtures prior to CGH. From mixtures of normal lymphocytes with triploid K‐562 cells the individual components were sorted according to stemline DNA content and processed by CGH in comparison with pure K‐562 samples and the original mixtures. Compared with 30 autosome copy number imbalances found in pure K‐562 samples, a mixture with 32% K‐562 cells showed 16 imbalancies, and none were detected in mixtures with 13% or 5% K‐562 cells. In contrast, 29, 22 and 23 imbalances were detected in K‐562 nuclei sorted from the 32%, 13% and 5% mixtures, respectively. This indicate that CGH analysis of flow sorted DNA aneuploid subpopulations enables a specific cytogenetic analysis of the individual subclones in a DNA heteroploid cell population.